Values and occupational choose - Furfari, Angela; Brito, Sílvio; Caggiano, Valeria (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Several studies demonstrate that Schwartz’s (2006) theory of human values is valid in cultures previously beyond its range. We measured the 10 value constructs in the theory with the Portrait Values Questionnaire (PVQ), a new and less abstract method. This study explores the influence of values in a professional choose, focusing on the associations between social and professional background. The findings support the construct validity of the test. The results suggest, there is a matching between values and occupational choose, there are evident differences between gender and age. These results confirm the international literature about different gender and value system’s. Its theoretical meaning in the context of Schwartz’s culture-level value theory is discussed.